Digital communication tools and memory tourism in Armero - Jorge Alexander Mora Forero, PhD (c); Angie Lorena Salgado Moreno; Yised Daniela Moreno Roldan (Comhumanitas)
The present research carries out a process of inquiry in order to describe the events of the Armero tragedy, which occurred on November 13, 1985, in Colombia. The objective of this study is to generate technological content to encourage memory tourism in Armero. The categories addressed by this research are those of technological tourism and memory tourism based on the history before, during, and after the tragedy. This study analyzes how to generate technological content to encourage memory tourism in Armero. The approach of this research is qualitative, and the types of research used in this project are descriptive and auditive. Interviews were used to describe the history of Armero through a podcast. The results describe the history of Armero using a digital communication tool such as the podcast, and data collection was carried out before, during, and after the tragedy of Armero was taken into account. This research contributes to the community of Armero and to the digital communication community about the history before, during, and after the tragedy. In conclusion, keeping the memory of Armero alive is an act of respect and recognition for the people who lost their lives and their families who suffered an irreparable loss.